Sleep disturbances in Parkinson's disease are associated with central parkinsonian pain - Vila-Chã, N. (2019)
Introduction: Sleep disturbances and pain are common non-motor symptoms in Parkinson's disease (PD). This study aimed to explore the association between these two symptoms in a cohort of patients with PD. Materials and methods: The Parkinson's Disease Sleep Scale (PDSS-2) was used to identify sleep disturbances in a series of 229 PD patients. The identification and characterization of pain was performed by a semi-structured interview and by the application of the Ford classification and the Brief Pain Inventory (BPI). The Unified Parkinson's Disease Rating Scale-III, Hoehn & Yahr (H&Y), and Schwab and England Independence Scale were used to assess motor symptoms and functional independence in off and on conditions. The Hospital Anxiety and Depression Scale (HADS) and SF-36 were applied to screen for anxiety and depression and to evaluate the quality of life. Non-parametric tests were used for group comparisons and logistic regressions were applied to explore predictors of sleep disturbances. Results: Seventy-five (33%) patients had clinically relevant sleep disturbances (PDSS-2≥18) and 162 patients (71%) reported pain. Of those with pain, 38 (24%) had central parkinsonian pain. PD patients with sleep disturbances experienced more pain and had more severe motor symptoms, lower functional independence, more anxiety and depression symptoms, and worst quality of life. Among patients with pain, central parkinsonian pain was the subtype of pain with the highest odds of sleep disturbances, even when taking into account motor symptoms (H&Y off), motor fluctuations, intensity of pain (BPI), and symptoms of anxiety and depression (HADS). Conclusions: The association between pain and sleep disturbances in PD appears to be dependent on subtype of pain. The close relationship between central parkinsonian pain and sleep disturbances in PD raises the possibility of common pathophysiological mechanisms. A better understanding of the relationship between sleep disturbances and central parkinsonian pain may contribute to the development of new care strategies in PD patients.